Peran Mahasiswa KKN UINSU terhadap Penerapan Desa Inklusif di Desa Kuala Indah - Nurhidayati; Siti Ismahani; Thorieq Al Abdu; Kamarulla Rambe; Siti Nurhaliza (Pusat Riset dan Inovasi Nasional, 2025)
Kuala Indah Village in Sei Suka, Batubara, North Sumatra, is a coastal village whose economy relies on fisheries and aquaculture. The community is predominantly Muslim and also practices small-scale agriculture and animal husbandry. The Community Service Program (KKN) provides a platform for students to apply academic theory in real-world contexts, while also encouraging active community involvement. KKN students implement various programs, such as stunting prevention, religious moderation, skills training for poverty alleviation, and education for children and adolescents. They also play a role in increasing community participation through cultural activities and supporting local businesses by strengthening digital visibility. These initiatives support the creation of inclusive villages, providing equal access and opportunities regardless of gender, religion, or socioeconomic status. This collaborative approach reinforces the value of mutual cooperation and enriches social and educational life in the village. Through KKN, universities demonstrate their tangible contribution to village development. The success of this program underscores the importance of social inclusion and collective work in promoting sustainable development in rural areas like Kuala Indah.